Current targeted therapies in the treatment of advanced colorectal cancer: a review. (July 2016) - Moriarity, Andrew; O'Sullivan, Jacintha; Kennedy, John; Mehigan, Brian; McCormick, Paul
Treatment strategies for metastatic colorectal cancer (mCRC) patients have undergone dramatic changes in the past decade and despite improved patient outcomes, there still exist areas for continued development. The introduction of targeted agents has provided clinicians with additional treatment options in mCRC, however, results have been mixed at best. These novel therapies were designed to interfere with specific molecules involved in the cellular carcinogenesis pathway and ultimately deliver a more focused treatment. Currently, their use in mCRC has been limited primarily as an adjunct to conventional chemotherapy regimens. This review explores the relevant cell-signaling networks in colorectal cancer, provides focus on the current targeted agent armamentarium approved for use in mCRC and explores the usefulness of predictive mCRC biomarkers.